Prediksi Zona Tangkapan Ikan Menggunakan Citra Klorofil-a Dan Citra Suhu Permukaan Laut Satelit Aqua MODIS Di Perairan Pulo Aceh - Mursyidin Mursyidin; Khairul Munadi; Muchlisin Z.A. (Universitas Syiah Kuala, 2015)
Fishing ground or fishing zone is a waters area which become a destination for fishing. Theprediction of fishing zone can be done by detecting chlorophyll-a and sea surface temperature distribution of Aqua MODIS Imagery. The aim of this study is to predict fishing zone on the waters of Pulo Aceh based on the chlorophyll distribution and sea surface temperature by utilizing the data of Aqua MODIS Satellite Imagery level 3. The stages of this study included collecting imagery, cutting the image according to the desired area, giving lands mark to display a more informative image, extracting information of chlorophyll-a and the distribution of sea surface temperature, and interpolating by using Kriging method. The highest distribution of chlorophyll-a happened in June and August, the spread moved from the the North Pulo Aceh to the South. The distribution of sea surface temperature that suitable for fishing was detected in August around the North Ujung Pulo Breuh and around pulau Keureusik. The potential zone of fishing on the waters of Pulo Aceh was only detected in August in the eastern of pulau Keureusik to Ujong Keumuroh. Pulo Aceh waters is suitable for fishing destination in August.